Predictors of Intimate Partner Violence Victimization by Multiple Partners Over a Period of 8 Years. Issue 1 (13th August 2021) - Stein, Sara F.; Galano, Maria M.; Grogan‐Kaylor, Andrew C.; Clark, Hannah M.; Ribaudo, Julie M.; Graham‐Bermann, Sandra A.
Abstract: Intimate partner violence (IPV) is a pervasive social issue with broad physical and mental health implications. Although 35%–56% of women report IPV victimization with more than one violent partner, few studies have identified factors that increase the risk of experiencing IPV across multiple partners (i.e., IPV reengagement). In the current study, multilevel modeling was used to examine the roles of trauma exposure, mental health, and sociodemographic factors in the risk for reengagement in a sample of women ( N = 120) with IPV victimization. Participants were drawn from a randomized control trial of an intervention for mothers who had experienced IPV. The results revealed that more psychological but less sexual IPV was associated with increased reengagement. Higher degrees of posttraumatic reexperiencing symptoms were associated with less reengagement. Depressive symptoms were also significantly associated with reengagement such that lower levels of positive affect and increased somatic symptoms were associated with increased reengagement. Higher income levels and less housing instability were associated with more reengagement, βrange = −.13–.16. Finally, compared to the control condition, participation in the intervention program was significantly associated with lower levels of reengagement at 8‐year follow‐up, β = −.75, p = .001. These findings suggest that it is not what happened (i.e., experiences of abuse) but rather a woman's posttraumatic experience (i.e., posttraumatic stress and depressive symptoms) that creates risk for reengagement. The findings support the long‐term effectiveness of a brief intervention in reducing reengagement.